Die Brüder David und Erwin Grimm: zwischen der Universität und dem Ministerium (Hyperboreus, 2016)
The article tells about lives of two Petersburg professors: David Grimm, a specialist for Roman Law, and his brother historian Erwin Grimm. Both of them were rectors of the St Petersburg University in a very difﬁcult time between revolutions, being a buffer between students and professors from one side and the Ministry of education from another. On the basis of other scholars’ works (ﬁrst of all those by O. Belyaeva) the author tries to show that David Grimm could resign to show his protests while his brother Erwin Grimm could not afford even this.